Adherence to option B + antiretroviral therapy and associated factors in pregnant and breastfeeding women in Sub-Saharan Africa: a systematic review and meta-analysis - (:unkn) unknown (My University, 2024)
Background To assess the adherence to option B + antiretroviral therapy (ART) and associated factors in pregnant and breastfeeding women in Sub-Saharan Africa (SSA). Methods We conducted a comprehensive search from 01 st January 2012 to 03 rd October 2022, across four databases: PubMed, Scopus, Proquest Central, and Index Medicus Africain, to identify studies focused on pregnant and/or breastfeeding women living with HIV and receiving option B+ ART in SSA. Studies reporting adherence data were included in the meta-analysis. Were excluded studies published before 01 st January 2012, grey literature, systematic reviews, and meta-analysis studies. Articles selection and data extraction were performed independently by two reviewers. We evaluated pooled adherence and pooled association between various factors and adherence using a random-effects model. Results Overall, 42 studies involving 15,158 participants across 15 countries contributed to the meta-analysis. The overall pooled adherence was 72.3% (95% CI: 68.2-76.1%). Having high education level (pooled odds ratio (OR): 2.25; 95% CI: 1.57-3.21), living in urban area (pooled OR: 1.75; 95% CI: 1.10-2.81), disclosing status to a family/partner (pooled OR: 1.74; 95% CI: 1.27-2.40), having a support system (pooled OR: 3.19; 95% CI: 1.89-5.36), receiving counseling (pooled OR: 3.97; 95% CI: 2.96-5.34), initiating ART at early clinical HIV stage (pooled OR: 2.22; 95% CI: 1.08-4.56), and having good knowledge on PMTCT/HIV (pooled OR: 2.71; 95% CI: 1.40-5.25) were factors significantly associated with adherence to option B + ART. Conclusions Despite the implementation of option B+ ART, the level of adherence among pregnant and breastfeeding women in SSA falls short of meeting the critical thresholds
Keywords: African Research